KEUNGGULAN BERSAING DAN MODAL INTELEKTUAL - Ganjar Garibaldi (Center for Economic Studies Universitas Katolik Parahyangan, 2006)
Competitive advantage and intellectual capital are important factors in managing business organizations. This research analyzed correlation between Competitive advantage and intellectual capital. There are two purposes of this research: (1) to analyze the meaning of competitive advantage, and the meaning of intellectual capital, (2) to analyze the correlation between them. This is a literature study. This study found that the company should develop their human resources to become more competitive.